2021
DOI: 10.1093/braincomms/fcab054
|View full text |Cite
|
Sign up to set email alerts
|

Secreted therapeutics: monitoring durability of microRNA-based gene therapies in the central nervous system

Abstract: The preclinical development of microRNA-based gene therapies for inherited neurodegenerative diseases is accompanied by translational challenges. Due to the inaccessibility of the brain to periodically evaluate therapy effects, accessible and reliable biomarkers indicative of dosing, durability and therapeutic efficacy in the central nervous system are very much needed. This is particularly important for viral vector-based gene therapies, in which a one-time administration results in long-term expression of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…17,49,50 In addition, a recent study confirmed that amiRNAs are present in vesicles 2 years post injection into the brains of NHPs. 51 These results support the choice of AAV5 as a delivery vehicle for amiR136-A2; however, the high variability in the silencing efficiency between individuals and the low silencing efficiency in the cortex suggest that the delivery and distribution of RNAi vectors in the brain should be improved. The uneven distribution of amiR136-A2 may be a cause of the weak improvements in motor deficits.…”
Section: Discussionmentioning
confidence: 80%
“…17,49,50 In addition, a recent study confirmed that amiRNAs are present in vesicles 2 years post injection into the brains of NHPs. 51 These results support the choice of AAV5 as a delivery vehicle for amiR136-A2; however, the high variability in the silencing efficiency between individuals and the low silencing efficiency in the cortex suggest that the delivery and distribution of RNAi vectors in the brain should be improved. The uneven distribution of amiR136-A2 may be a cause of the weak improvements in motor deficits.…”
Section: Discussionmentioning
confidence: 80%
“…Human iPS cells (ND42229*B) containing 71 CAG repeats were reprogrammed from HD patient-derived fibroblasts (Coriell Institute Stem Biobank, Camden, NJ, USA) [ 47 ]. These cells were differentiated and maintained in culture as previously described [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of EVs from HEK293-miHTT cell line conditioned culture media was performed as previously described [ 47 ]. Briefly, culture medium was collected and centrifuged at 4000× g for 15 min at room temperature to remove cells and cell debris.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations